2019
DOI: 10.3847/1538-3881/ab1b30
|View full text |Cite
|
Sign up to set email alerts
|

Variability in the Atmosphere of the Hot Jupiter Kepler-76b

Abstract: Phase curves and secondary eclipses of gaseous exoplanets are diagnostic of atmospheric composition and meteorology, and the long observational baseline and high photometric precision from the Kepler Mission make its dataset well-suited for exploring phase curve variability, which provides additional insights into atmospheric dynamics.Observations of the hot Jupiter Kepler-76b span more than 1,000 days, providing an ideal dataset to search for atmospheric variability. In this study, we find that Kepler-76b's s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 38 publications
0
47
1
Order By: Relevance
“…Furthermore, when the conductivity is allow to change due to large daynight temperature difference, Rogers (2017) show that the direction of the zonal jet can start to oscillate, leading to a variation in the hot spot offset of up to 20 degrees. Such a large variation in the hot spot offset may be responsible for the time variability observed in the Kepler phase curves of two hot Jupiters Jackson et al 2019).…”
Section: Magnetic Couplingmentioning
confidence: 97%
See 1 more Smart Citation
“…Furthermore, when the conductivity is allow to change due to large daynight temperature difference, Rogers (2017) show that the direction of the zonal jet can start to oscillate, leading to a variation in the hot spot offset of up to 20 degrees. Such a large variation in the hot spot offset may be responsible for the time variability observed in the Kepler phase curves of two hot Jupiters Jackson et al 2019).…”
Section: Magnetic Couplingmentioning
confidence: 97%
“…Clear sky models of hot Jupiters are predicted to vary by less than 1% in their global temperature ; Rauscher and Menou 2012b; Komacek and Showman 2020), which would not lead to observational evidence given current observational facilities. Optical phase curves, however, have been shown to vary significantly for two planets Jackson et al 2019). Although the source of the time variation is still under debate, and possibly includes magnetic coupling between the winds and the planetary magnetic field (Rogers and Komacek 2014;Rogers 2017) it has been postulated that the presence of clouds could significantly enhance the observable variability (Lines et al 2018).…”
Section: Clouds and Atmospheric Variabilitymentioning
confidence: 99%
“…GCMs have predicted hot Jupiter atmospheric variability due to propagating waves and instabilities on spatial scales of thousands of kilometers to global scales (Dobbs-Dixon et al, 2010;Komacek & Showman, 2020;Lines et al, 2018b;Parmentier et al, 2013), which could lead to temporal variations in the spatial distribution of aerosols. Brightness variability has also been detected on hot Jupiters (Armstrong et al, 2016;Jackson et al, 2019), with interpretations ranging from clouds reacting to changing winds and temperatures to the coupling of atmospheric circulation with the planets' magnetic fields (Rogers, 2017;Rogers & Komacek, 2014).…”
Section: Future Observationsmentioning
confidence: 99%
“…Mutually discrepant secondary eclipse depths have been reported at various optical wavelengths (López-Morales et al 2010;Föhring et al 2013;Hooton et al 2019;von Essen et al 2019), as well as in the 2 µm region (Zhao et al 2012;Crossfield et al 2012;Croll et al 2015). In light of other purported detections of atmospheric variability in hot Jupiters (e.g., Armstrong et al 2016;Jackson et al 2019; but also see Lally & Vanderburg 2020), the question of whether these differences are real or are instead caused by instrumental effects and/or observing conditions has come to the fore. Meanwhile, recent theoretical work on the atmospheric dynamics of hot Jupiters has shown that hydrodynamic instabilities and other transient atmospheric processes may lead to orbit-to-orbit evolution in the global average temperature, the effects of which may be detectable with current and near-future instruments (e.g., Tan & Komacek 2019;Komacek & Showman 2020;Tan & Showman 2020).…”
mentioning
confidence: 99%